Histoacryl Glue Injection for Treatment in Patient with Gastric Varices Non-cirrhotic Portal Hypertension - Jualita Heidy Saputri; Budi Widodo (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2018)
Upper gastrointestinal bleeding is differentiated based on clinical needs into variceal and non-variceal bleeding. The cause of varices bleeding is portal hypertension, both cirrhosis and non-cirrhosis. Gastric varices occur less than esophageal varices, but the morbidity and mortality rate are high. The following is case report of gastric non-cirrhotic variceal bleeding. The 19-year-old man had hematemesis melena with anemia. After hemodynamic stabilization, GOV 2 gastric varices were found and definitive endoscopic obturation therapy was given by intravarices injection of diluted histoacryl. After the procedure, there were mild and transient side effects, as well as no re-bleeding until the 7th month.